Governor of Bali : Tumpek Krulut as momentum to cherish love for Balinese - Eka Ari Suhendra (Bali Tourism Board, 2021)
The word Tumpek refers to the meeting of the five-day wewaran system (Panca Wara), namely Kliwon, with the seven-day wewaran (Sapta Wara) system, namely Saniscara or Saturday. The five-day wewaran, seven-day wewaran, and pawukon cycle encounter gave birth to the concept of Tumpek as a day of celebration of objects and creatures that have an important role in human life. Pawukon determines the suffix of the tumpek, which takes place twice a year. For example, if the Tumpek falls on Pawukon Uye will be called Tumpek Uye, then the Tumpek that falls on pawukon Krulut will be called Tumpek Krulut. On Tumpek Krulut, Balinese Hindus worship His manifestation as Lord Iswara. A deity, lord of sacred sounds creation. Some scholars argue that the word Krulut, comes from the word Lulut which means affection love. Balinese ancestors adapted this term from the old Javanese calendar. Later, the word krulut in Tumpek Krulut is associated with celebration of love. In February 2022, The Governor of Bali, Wayan Koster considered Tumpek Krulut as the Balinese day of love. As the same as Valentine’s Day celebrations in this era. Wayan Koster emphasized that Hindus and Balinese people can use the Tumpek Kerulut as indigenous momentum to cherish love.